2020
DOI: 10.3390/ijms21124225
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NF-κB by the Cell-Permeable NEMO-Binding Domain Peptide Improves Albuminuria and Renal Lesions in an Experimental Model of Type 2 Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a multifactorial disease characterized by hyperglycemia and close interaction of hemodynamic, metabolic and inflammatory factors. Nuclear factor-κB (NF-κB) is a principal matchmaker linking hyperglycemia and inflammation. The present work investigates the cell-permeable peptide containing the inhibitor of kappa B kinase γ (IKKγ)/NF-κB essential modulator (NEMO)-binding domain (NBD) as therapeutic option to modulate inflammation in a preclinical model of type 2 diabetes (T2D) with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Previous studies have also shown that Zn administration reduces NF-κB activation and ameliorates vascular endothelial cell dysfunction ( 25 ). NF-κB is an important pro-inflammatory mediator in patients with DN, with its activation resulting in the production of a variety of pro-inflammatory cytokines, the proliferation, and hypertrophy of mesangial cells, and tubulointerstitial fibrosis ( 26 ). Specifically, NF-κB activation results in greater release of TNF-α, IL-6, and IL-8, and in turn, TNF-α increases the production of IL-1, IL-6, IL-8, and IL-18 ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that Zn administration reduces NF-κB activation and ameliorates vascular endothelial cell dysfunction ( 25 ). NF-κB is an important pro-inflammatory mediator in patients with DN, with its activation resulting in the production of a variety of pro-inflammatory cytokines, the proliferation, and hypertrophy of mesangial cells, and tubulointerstitial fibrosis ( 26 ). Specifically, NF-κB activation results in greater release of TNF-α, IL-6, and IL-8, and in turn, TNF-α increases the production of IL-1, IL-6, IL-8, and IL-18 ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a bridge linking inflammation and hyperglycemia. A Cell-permeable peptide, designing with the inhibitor of kappa B kinase γ (IKKγ)/NF-κB essential modulator (NEMO)-binding domain (NBD), alleviates the albuminuria, kidney damage, podocyte loss and GBM thickness in DKD rat models (Opazo-Rios et al., 2020 ).…”
Section: Targeted Drug Delivery Strategy In Dkdmentioning
confidence: 99%
“…Persistent hyperglycemia causes inflammation, endothelial dysfunction, and oxidative stress in the kidneys and, thus, is partly associated with DKD progression [ 8 , 9 , 10 ]. In addition to traditional hypoglycemic agents and insulin, several agents targeting peptidyl hormones, such as dipeptidyl peptide IV and glucagon-like peptide-1, have recently been introduced for the treatment of hyperglycemia [ 11 ].…”
Section: Diabetic Kidney Disease and The Treatment Strategymentioning
confidence: 99%